A Poetry Pedagogy for Teachers: Reorienting Classroom Literacy Practices - Loch, Sarah (Art/Research International)

(untitled) (University of Alberta, 2023)
This is a review of A Poetry Pedagogy for Teachers: Reorienting Classroom Literacy Practices by Maya Pindyck and Ruth Vinz, with Diana Liu and Ashlynn Wittchow. The authors, U.S-based poets, educators, and arts-academics, share a crafted master class in creative thinking and poetic confidence building for teachers. They employ a strongly collaborative stance, and take readers with them on a poststructural journey by weaving together a collection of poems, scholarly literature, and resources which aim to provoke their teacher-readers to write. Readers should ready themselves with pen and paper, notebook, or computer as the many ”Invitations” (writing exercises which appear at the end of each chapter and in a section of their own towards the end) will have readers sliding into poetry and seeing it in the most unexpected places.